2010
DOI: 10.1227/neu.0b013e3181f742b2
|View full text |Cite
|
Sign up to set email alerts
|

Corticotomy Closure Avoids Subdural Collections After Hemispherotomy

Abstract: We recommend closing ventricular access after functional hemispherotomy, notably in patients who have had a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Possible explanations for the better result in our patients may be the above-mentioned extensive irrigation of the ventricular system, and the closure of the corticotomy tunnel with fibrin flue and Lyostypt, which helped to restore a normal CSF circulation. This assumption is supported by reports from other centers, where postoperative subdural hygroma formation was reported to be avoided by closure of the corticotomy with fibrin glue (Blauwblomme & Harkness, 2010). Another factor might be the higher rate of MCD patients in the series of Delalande (36%) compared with our series (27.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Possible explanations for the better result in our patients may be the above-mentioned extensive irrigation of the ventricular system, and the closure of the corticotomy tunnel with fibrin flue and Lyostypt, which helped to restore a normal CSF circulation. This assumption is supported by reports from other centers, where postoperative subdural hygroma formation was reported to be avoided by closure of the corticotomy with fibrin glue (Blauwblomme & Harkness, 2010). Another factor might be the higher rate of MCD patients in the series of Delalande (36%) compared with our series (27.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Involvement of the basal ganglia and/or thalamus in the resection may predispose to hydrocephalus because such techniques can involve broad exposure of the lateral ventricle to blood products. Recently, Blauwblomme and Harkness (2010) reported on 16 patients undergoing hemispherotomy surgery with closure of the ventricular cavity using fibrin glue and pial sutures. Their technique includes resection of the basal ganglia with broad intraoperative exposure of the lateral ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Subdural collections are directly related to opening of the ventricles that is mandatory in all disconnection techniques, while they may be prevented by closure of the CSF access by fibrin glue. 15…”
Section: Discussionmentioning
confidence: 99%
“…Subdural collections are directly related to opening of the ventricles that is mandatory in all disconnection techniques, while they may be prevented by closure of the CSF access by fibrin glue. 15 While etiologies and contralateral MRI abnormalities are consensual predictive factors for seizure freedom after hemispherotomy, the impact of the surgical approach on seizure outcomes is still debated. Indeed, if the post hoc analysis of the Hemispherotomy Outcome Prediction Scale study showed an odds ratio of 3.67 for seizure recurrence when comparing lateral with vertical hemispherotomy, the difference in the sample size (600 in the lateral group vs72 in the vertical) questions the validity of the statistical analysis.…”
Section: Limitationsmentioning
confidence: 99%